Molecular Epidemiology and Risk Factors of Carbapenemase-Producing Enterobacteriaceae Isolates in Portuguese Hospitals: Results From European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE) - Manageiro, Vera; Romão, Raquel; Moura, Inês Barata; Sampaio, Daniel A.; Vieira, Luís; Ferreira, Eugénia; , the Network EuSCAPE-Portugal; Caniça, Manuela (Frontiers in Microbiology, 2018)
In Portugal, the epidemiological stage for the spread of carbapenemase-producing Enterobacteriaceae (CPE) increased from sporadic isolates or single hospital clones (2010-2013), to hospital outbreaks, later. Here we report data from a six-month study performed under the European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE). During the study period, 67 isolates (61 K. pneumoniae and 6 E. coli) non-susceptible to carbapenems were identified in participant hospital laboratories. We detected 37 blaKPC-type (including one new variant: blaKPC-21), 1 blaGES-5, and 1 blaGES-6 plus blaKPC-3, alone or in combination with other bla genes. Bioinformatics analysis of the KPC-21-producing E. coli identified the new variant blaKPC-21 in a 12,748 bp length plasmid. The blaKPC-21 gene was harbored on a non-Tn4401 element, presenting a partial ISKpn6 (ΔISKpn6/ΔtraN) with the related left IR (IRL) upstream and with a truncated Tn3 transposon downstream. PFGE and MLST analysis showed an important diversity, as isolates belonged to distinct PFGE and STs profiles. In this study, he highlighted the presence of the high-risk clone E. coli sequence-type (ST)131 clade C/H30. This worldwide disseminated E. coli lineage was already detected in Portugal among other antibiotic resistance reservoirs. This study highlights the intra- and inter-hospital spread and possible intercontinental circulation of CPE isolates.